High-ion-flux composite material, preparation method, solid electrolyte membrane and battery
Through the combination of non-metal cation-modified garnet electrolyte and acrylate copolymer, the problem of poor conductivity and compatibility in the composite solid electrolyte membrane is solved, the high ion flux and mechanical strength are improved, and the lithium-ion battery is improved performance.
Patent Information
- Application Number
- CN202411249049.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2024-12-27
AI Technical Summary
The existing composite solid electrolyte membranes have problems such as poor conductivity and poor compatibility of ceramic electrolytes with polymers in lithium-ion batteries, which affect the lithium ion transmission and the overall performance of the battery.
The garnet electrolyte modified with non-metallic cations is combined with acrylate copolymer to form a high ion flux composite material through ion exchange and curing and polypolymerization reaction, which improves lithium ion conductivity and mechanical strength, and enhances the interface phase through hydrogen bonding. Capacity.
The composite material with high ion flux is achieved, the lithium ion conductivity and mechanical strength is improved, the film forming performance of the electrolyte membrane is enhanced, the initiator residue is avoided, and the overall performance of the battery is improved.
Smart Images

Figure CN119208708A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a high ion flux composite material, a preparation method, a solid electrolyte membrane and a battery. Background Art
[0002] As one of the most important energy storage devices, lithium-ion batteries have been widely used in people's production and life. However, traditional lithium-ion batteries use organic liquid electrolytes, which have safety hazards such as strong side reactions between electrodes and electrolytes, narrow applicable temperature range, and flammability and explosion.
[0003] In order to solve the problems of traditional liquid electrolytes, solid electrolytes have attracted attention as a potential solution. Solid electrolytes include inorganic solid electrolytes and polymer electrolytes. Inorganic solid electrolytes such as lithium-containing garnet (LLZO) have the advantages of strong stability and high room temperature conductivity, but they have shortcomings such as large interface resistance to metallic lithium, unstable cycles, and poor flexibility. Although polymer electrolytes have good viscoelastic deformation ability, their low lithium ion conductivity, poor electrochemical stability, and mechanical stability limit their practical applications.
[0004] In order to overcome the limitations of inorganic solid electrolytes and polymer electrolytes, researchers began to explore the uniform dispersion of ceramic phases with high lithium ion conductivity on polymer matrices to develop flexible ceramic / polymer composite solid electrolytes. This composite solid electrolyte combines the high ion conductivity of ceramic electrolytes and the good viscoelastic deformation ability of polymer electrolytes, providing a new direction for the research and development of solid-state lithium batteries.
[0005] There are many technologies for studying composite solid electrolytes, but they all have various problems.
[0006] For example, some related technologies disclose the use of electrospinning technology to prepare a three-dimensional porous framework as a matrix for a composite electrolyte. Although this method can increase the strength of the composite electrolyte, the introduction of an inert skeleton will not only reduce the overall ionic conductivity, but also affect the interface impedance. Moreover, the use of electrospinning technology greatly increases the cost and is difficult to industrialize. In addition, AI BN thermal initiator is introduced during in-situ polymerization. If the reaction is incomplete, the initiator will remain, resulting in a decrease in the overall electrochemical performance.
[0007] For example, some related technologies disclose the use of a dry process to prepare a composite electrolyte, wherein the composite electrolyte flocculent mixture is repeatedly rolled on a double-roller mill at 80°C, and thinned to 50 μm in turn to obtain a composite solid electrolyte membrane. Although this method can form a membrane, the bonding between the ceramic electrolyte and the polymer is not tight enough, which seriously affects the transmission of lithium ions. In addition, the dry process will lead to extremely large interface impedance. During battery assembly, only a large pressure can be used to maintain good contact at the interface, which places great demands on battery materials and processes. Summary of the invention
[0008] The embodiments of the present application provide a high ion flux composite material, a preparation method, a solid electrolyte membrane and a battery to solve the problems of poor conductivity of the electrolyte membrane and poor compatibility between the ceramic electrolyte and the polymer in the related art.
[0009] In a first aspect, a high ion flux composite material is provided, which includes a non-metal cation-modified garnet electrolyte and a binder, wherein the binder includes an acrylate copolymer and a lithium salt.
[0010] In some embodiments, calculated by mass fraction, the non-metallic cation-modified garnet electrolyte is 80-95%, and the binder is 5-20%.
[0011] In some embodiments, the non-metallic cation comprises NH4 + PH4 + One or more of the .
[0012] In some embodiments, the molar ratio of the non-metallic cation to the garnet electrolyte is (30-100):1.
[0013] In some embodiments, the garnet electrolyte is an amorphous garnet electrolyte nanopowder formed by crushing a single crystal garnet electrolyte.
[0014] In some embodiments, the garnet electrolyte includes LGLZO electrolyte Li 6.4 Ga 0.2 La3Zr2O 12 ,LLZO electrolyte Li7La3Zr2O 12 and LLZTO electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 One or more of the .
[0015] In some embodiments, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonyl imide), and lithium bis(fluorosulfonyl imide).
[0016] In some embodiments, the lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
[0017] In some embodiments, the mass fraction of the lithium salt in the adhesive is 25% to 35%.
[0018] In some embodiments, the acrylate copolymer includes a monomer, a crosslinker and a plasticizer, wherein the monomer, the crosslinker and the plasticizer all have an acrylic group, and the molar ratio of the monomer, the crosslinker and the plasticizer is (10-12):(3-5):(3-5).
[0019] In some embodiments, the molar ratio of the crosslinking agent to the plasticizer is 1:1.
[0020] In some embodiments, the monomer includes one or more of hexafluorobutyl acrylate, 3-(N,N-dimethylamino)ethyl acrylate, methyl 2-cyanoacrylate, and azoacrylate.
[0021] In some embodiments, the crosslinking agent includes one or more of ethyl acrylate, butanediol dimethacrylate, ethylene glycol dimethacrylate, and trimethylolacrylate.
[0022] In some embodiments, the plasticizer includes one or more of lauryl acrylate, 2-methyl methacrylate, methyl acrylate, ethyl acrylate, and isooctyl acrylate.
[0023] In a second aspect, a method for preparing a high ion flux composite material as described above is provided, comprising:
[0024] Adding the non-metal cation-modified garnet electrolyte to the precursor solution of the adhesive and mixing well;
[0025] The heating is performed to effect a curing polyaddition reaction to obtain a high ion flux composite material.
[0026] In some embodiments, the heating temperature of the curing addition polymerization reaction is 90-120° C., and the heating time is 4-7 hours.
[0027] In some embodiments, the preparation steps of the non-metal cation modified garnet electrolyte include:
[0028] Amorphous garnet electrolyte nanopowder formed by crushing single crystal garnet electrolyte;
[0029] dispersing amorphous garnet electrolyte nanopowder into a modification solution containing non-metallic cations and stirring;
[0030] The garnet electrolyte modified by the non-metal cation is obtained by washing with a volatile solvent and drying.
[0031] In some embodiments, the acrylate copolymer includes a monomer, a cross-linking agent and a plasticizer, and the monomer, the cross-linking agent and the plasticizer all have an acrylic acid group. The steps of preparing the precursor solution of the adhesive include:
[0032] The monomer, cross-linking agent, plasticizer and lithium salt are stirred and mixed evenly under light-proof conditions and allowed to stand.
[0033] In a third aspect, a solid electrolyte membrane is provided, which comprises any high ion flux composite material as described above.
[0034] In a fourth aspect, a battery is provided, which comprises the solid electrolyte membrane as described above.
[0035] The beneficial effects of the technical solution provided by this application include:
[0036] The present application provides a high ion flux composite material, preparation method, solid electrolyte membrane and battery. In the composite material provided by the present application, the garnet electrolyte is modified by non-metallic cations, that is, after the garnet electrolyte is put into the modification solution containing non-metallic cations, the lithium ions in the garnet electrolyte can exchange ions with the non-metallic cations in the modification solution, and the non-metallic cations are pinned on the lithium vacancies of the garnet electrolyte, thereby obtaining a garnet electrolyte modified by non-metallic cations. After the modified garnet electrolyte is put into the prepared precursor solution of the adhesive, a curing addition polymerization reaction is carried out to obtain a composite material with high ion flux, wherein the non-metallic cation can not only act as an initiator to initiate the addition polymerization reaction of the raw materials of the acrylate copolymer, and ensure that there is no residual initiator after the copolymerization is completed; the non-metallic cation can also form hydrogen bonds with the copolymer to ensure the stable intercalation between garnet / copolymer, improve the interface compatibility between the two, thereby enhancing the tensile strength and improving the film-forming performance; and the non-metallic cation can also act as a lithium ion migration skeleton to construct a high-flux ion channel, effectively improving the lithium ion conductivity of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0038] Figure 1 The ionic conductivity measurement results provided in the embodiments of the present application;
[0039] Figure 2 The stress-strain diagram provided for the embodiments of the present application. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.
[0041] The embodiment of the present application provides a high ion flux composite material, which includes a non-metal cation-modified garnet electrolyte and a binder, wherein the binder includes an acrylate copolymer and a lithium salt.
[0042] In the composite material provided by the embodiment of the present application, the garnet electrolyte is modified by non-metallic cations, that is, after the garnet electrolyte is put into the modification solution containing non-metallic cations, the lithium ions in the garnet electrolyte can exchange ions with the non-metallic cations in the modification solution, and the non-metallic cations are pinned to the lithium vacancies of the garnet electrolyte, thereby obtaining a garnet electrolyte modified by non-metallic cations. After the modified garnet electrolyte is put into the precursor solution of the prepared adhesive, a curing addition polymerization reaction is carried out to obtain a composite material with high ion flux, wherein the non-metallic cation can not only act as an initiator, but also initiate the addition polymerization reaction of the raw materials of the acrylate copolymer, and ensure that there is no residual initiator after the copolymerization is completed; the non-metallic cation can also form hydrogen bonds with the copolymer to ensure the stable intercalation between garnet / copolymer, improve the interfacial compatibility between the two, thereby enhancing the tensile strength and improving the film-forming performance; and the non-metallic cation can also act as a lithium ion migration skeleton to construct a high-flux ion channel, effectively improving the lithium ion conductivity of the composite material.
[0043] The reason why the acrylic acid ester copolymer is used in the adhesive is that it has high mechanical strength, which can ensure that the composite electrolyte membrane has good self-supporting ability, and it has good elasticity, which can solve the problem of volume expansion of the lithium negative electrode.
[0044] Furthermore, calculated by mass fraction, the non-metallic cation-modified garnet electrolyte is 80-95%, and the adhesive is 5-20%.
[0045] There are many optional types of non-metallic cations in the present application, for example, the non-metallic cations include NH4 + PH4 + One or more of the .
[0046] When the above non-metallic cation exists in the form of a salt, it may be NH4Cl, NH4NHO3, etc.
[0047] Furthermore, too little non-metallic cations will lead to insufficient initiators to make the raw materials of the acrylate copolymer unable to form an elastomer through addition polymerization, resulting in low tensile strength and elastic recovery rate of the electrolyte membrane; while too much non-metallic cations will affect lithium ion transport, resulting in a decrease in lithium ion conductivity, so the non-metallic cations need to be maintained in an appropriate amount so that the composite electrolyte can obtain the best performance. Therefore, the molar ratio of the non-metallic cations to the garnet electrolyte described in the present application is (30-100):1.
[0048] The garnet electrolyte in the present application may be in the form of particles. To further improve the performance, in the present application, the garnet electrolyte is in the form of nanopowder. Specifically, the garnet electrolyte is an amorphous garnet electrolyte nanopowder formed by crushing a single crystal garnet electrolyte.
[0049] The garnet electrolyte includes LGLZO electrolyte Li 6.4 Ga 0.2 La3Zr2O 12 ,LLZO electrolyte Li7La3Zr2O 12 and LLZTO electrolyte Li 6.5 Ln3Z 1.5 Ta 0.5 O 12 One or more of the .
[0050] It is preferred to use single crystal LGLZO electrolyte Li 6.4 Ga 0.2 La3Zr2O 12 .
[0051] There are many optional types of lithium salts in the present application. For example, the lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonylimide), and lithium bis(fluorosulfonylimide).
[0052] Preferably, the lithium salt is lithium bis(trifluoromethanesulfonyl imide).
[0053] In the adhesive, the mass fraction of the lithium salt is 25% to 35%, ensuring good ion conductivity.
[0054] The acrylate copolymer includes monomers, crosslinking agents and plasticizers of the same system, that is, the monomers, crosslinking agents and plasticizers all have acrylic acid groups, and the acrylate copolymer is a macromolecule formed by mutual addition polymerization between the same type of acrylic acid monomers initiated by free radicals generated by the decomposition of non-metallic cations by the monomers, crosslinking agents and plasticizers of the same system. The acrylate copolymer is polymerized by monomers, crosslinking agents and plasticizers of the same system, has no reaction by-products, and effectively avoids low electrochemical performance caused by by-products.
[0055] The molar ratio of the monomer, the crosslinking agent and the plasticizer is (10-12):(3-5):(3-5), and the molar ratio of the crosslinking agent and the plasticizer is 1:1.
[0056] The monomer includes one or more of hexafluorobutyl acrylate, 3-(N,N-dimethylamino)ethyl acrylate, 2-methylcyanoacrylate, and azoacrylate, and is preferably hexafluorobutyl acrylate.
[0057] The cross-linking agent includes one or more of ethyl acrylate, butanediol dimethacrylate, ethylene glycol dimethacrylate, and trimethylolacrylate, preferably ethyl acrylate.
[0058] The plasticizer includes one or more of lauryl acrylate, 2-methyl methacrylate, methyl acrylate, ethyl acrylate, and isooctyl acrylate, preferably lauryl acrylate.
[0059] The present application also provides a method for preparing a high ion flux composite material, which comprises the following steps:
[0060] 101: Add the non-metallic cation modified garnet electrolyte into the adhesive precursor solution and mix well.
[0061] 102: Heating to perform a curing polyaddition reaction to obtain a high ion flux composite material.
[0062] Wherein, in step 102, the heating temperature of the curing addition polymerization reaction is 90-120°C, and the heating time is 4-7h. Preferably, the heating temperature of the curing addition polymerization reaction is 100°C, and the heating time is 5h.
[0063] In step 101, the preparation steps of the non-metal cation modified garnet electrolyte include:
[0064] 201: Amorphous garnet electrolyte nanopowder formed by crushing single crystal garnet electrolyte.
[0065] 202: Dispersing amorphous garnet electrolyte nanopowder into a modification solution containing non-metallic cations and stirring.
[0066] 203: washing with a volatile solvent and drying to obtain the non-metal cation modified garnet electrolyte.
[0067] The volatile solvent in step 203 may be ethanol, and before washing with the volatile solvent, deionized water or the like may be used for washing.
[0068] In step 101, the acrylate copolymer includes monomers, a crosslinking agent and a plasticizer of the same system, and the preparation step of the precursor solution of the adhesive includes: stirring and mixing the monomers, the crosslinking agent, the plasticizer and the lithium salt in a light-proof condition to uniformly mix and let stand.
[0069] Among them, light protection can be achieved by using brown containers.
[0070] The embodiment of the present application also provides a solid electrolyte membrane, which is prepared by using a high ion flux composite material.
[0071] An embodiment of the present application also provides a battery, which includes the above-mentioned solid electrolyte membrane.
[0072] The present application is described in detail below through specific examples and comparative examples.
[0073] Example 1
[0074] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nano-scale powder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0075] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2) and 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle and heated at 40°C and stirred to mix well to accelerate the dissolution of the lithium salt, and then cooled and allowed to stand overnight.
[0076] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile are added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry. The purpose of adding solvents such as acetonitrile is to adjust the viscosity of the slurry for easy stirring. It is then poured on a polytetrafluoroethylene mold and kept warm at 50°C for 10h to remove the acetonitrile solvent. It is then kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0077] Example 2
[0078] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nano-scale powder. Disperse 0.1 mol LGLZO into 3 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0079] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) were added into a small brown bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0080] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0081] Example 3
[0082] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush the single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 10 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0083] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0084] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0085] Example 4
[0086] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0087] 2. Preparation of precursor solution: 12 mmol hexafluorobutyl acrylate (C7H6F6O2), 5 mmol ethyl acrylate (C5H8O2) and 5 mmol dodecyl acrylate (C 15 H 28 O2), 6.77 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0088] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0089] Example 5
[0090] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0091] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.07 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0092] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a solid electrolyte membrane.
[0093] Example 6
[0094] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0095] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 3.03 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0096] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution, and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then cast on a polytetrafluoroethylene mold. The acetonitrile solvent was removed by heat preservation at 50°C for 10h, and then the acetonitrile solvent was cured and polyaddition was carried out at 100°C for 5h to obtain a flexible solid electrolyte membrane.
[0097] Example 7
[0098] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0099] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0100] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.5g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0101] Example 8
[0102] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0103] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0104] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.11g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was cured and polyadded at 100°C for 5h to obtain a flexible solid electrolyte membrane.
[0105] Comparative Example 1
[0106] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 1 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0107] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0108] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it at 50°C for 10h, and then it was kept at 100°C for 5h for curing and polyaddition reaction. The electrolyte membrane was not formed.
[0109] Comparative Example 2
[0110] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 15 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0111] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0112] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0113] Comparative Example 3
[0114] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0115] 2. Preparation of precursor solution: 10 mmol hexafluorobutyl acrylate (C7H6F6O2), 7 mmol ethyl acrylate (C5H8O2) and 7 mmol dodecyl acrylate (C 15 H 28 O2), 7.08 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0116] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0117] Comparative Example 4
[0118] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0119] 2. Preparation of precursor solution: 15 mmol hexafluorobutyl acrylate (C7H6F6O2), 3 mmol ethyl acrylate (C5H8O2) and 3 mmol dodecyl acrylate (C 15 H 28 O2), 6.81 mmol lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) were added into a small brown bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0120] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it at 50°C for 10h, and then it was kept at 100°C for 5h for curing and polyaddition reaction. The electrolyte membrane was not formed.
[0121] Comparative Example 5
[0122] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0123] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 0.65 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a brown small bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0124] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0125] Comparative Example 6
[0126] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0127] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 4.82 mmol lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) were added into a small brown bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0128] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it at 50°C for 10 hours, and then it was kept at 100°C for 5 hours for curing and polyaddition reaction. The electrolyte membrane could not be formed.
[0129] Comparative Example 7
[0130] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0131] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0132] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 1.33g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it warm at 50°C for 10h, and then it was kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0133] Comparative Example 8
[0134] 1. Preparation of non-metal cation modified garnet electrolyte LGLZO@NH4 + :Use a high-energy ball mill in a glove box to crush single crystal LGLZO into nanopowder. Disperse 0.1 mol LGLZO into 5 mol / L NH4Cl ethanol solution (volume 1 L) and stir continuously for 10 h. Filter and wash three times with deionized water, and then filter and wash twice with alcohol, and dry at 50 ° C for 3 h to obtain pretreated LGLZO@NH4 + .
[0135] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) were added into a small brown bottle, heated at 40°C, stirred and mixed, and then cooled and allowed to stand overnight.
[0136] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.01g precursor solution and 5g acetonitrile were added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which was then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent was removed by keeping it at 50°C for 10 hours, and then it was kept at 100°C for 5 hours for curing and polyaddition reaction. The electrolyte membrane could not be formed.
[0137] Comparative Example 9
[0138] 1. Preparation of LGLZO: Single crystal LGLZO was crushed into nano-scale powder using a high-energy ball mill in a glove box.
[0139] 2. Preparation of precursor solution: 5 mmol hexafluorobutyl acrylate (C7H6F6O2), 1.5 mmol ethyl acrylate (C5H8O2) and 1.5 mmol dodecyl acrylate (C 15 H 28 O2), 2.52 mmol lithium bis(trifluoromethanesulfonyl imide) (LiTFSI) were added into a small brown bottle, heated at 40°C and stirred to mix, then cooled and allowed to stand overnight.
[0140] 3. Preparation of flexible solid electrolyte membrane: 2g LGLZO@NH4 + Powder, 0.22g precursor solution, 5g acetonitrile, and 0.5wt% azobisisobutyronitrile are added dropwise into a brown bottle and stirred evenly at room temperature to obtain a milky white slurry, which is then poured onto a polytetrafluoroethylene mold. The acetonitrile solvent is removed by keeping it warm at 50°C for 10h, and then it is kept warm at 100°C for 5h for curing and polyaddition reaction to obtain a flexible solid electrolyte membrane.
[0141] Performance Testing
[0142] 1. Electrochemical impedance test
[0143] The embodiment and the comparative example were assembled into a stainless steel symmetrical battery for testing, and the test results are shown in Table 1. The test method is as follows:
[0144] The test method of electrochemical impedance test is: use an electrochemical workstation to perform electrochemical impedance test on the battery at room temperature, the test frequency range is 0.01Hz~1MHz, the interference amplitude is 10mV, and the battery is left at room temperature for 12h before the test, and then the AC impedance of the battery is tested.
[0145] 2. Tensile strength
[0146] The test is based on the national standard GB1040. A gradually increasing tensile load is applied to the length direction of the standard sample of the composite film to cause it to deform until it is destroyed. The maximum tensile stress required for the sample to be destroyed is the tensile strength.
[0147] 3. Deformation rate
[0148] The test is based on the national standard GB1040. A gradually increasing tensile load is applied to the length direction of the composite film standard sample to cause it to deform until it is destroyed. The maximum tensile deformation required for the sample to fail is the deformation rate.
[0149] 4. Elastic recovery rate
[0150] The test is based on the national standard GB16776. A gradually increasing tensile load is applied to the length L0 direction of the composite film standard sample. It is stretched to 25% and its length L1 is measured. After it is left for 24 hours and relaxed, its length L2 is measured. (L1-L2) / (L1-L0) is the elastic recovery rate.
[0151] Test results see Figure 1 , Figure 2 As shown in Table 1 below.
[0152] Table 1 Ionic conductivity, tensile strength and elastic recovery rate of the embodiments and comparative examples
[0153]
[0154]
[0155] The ionic conductivity of Examples 1-8 is ≥1×10 -3 S / cm, indicating that this composite electrolyte has excellent ionic conductivity and can effectively carry out ion transmission; and its tensile strength is greater than 0.7Mpa, indicating that it has good mechanical strength, which can ensure that the composite electrolyte membrane can be independently formed without the need for additional supporting matrix or forming agent, thereby avoiding the reduction of electrochemical performance; in addition, its elastic recovery rate is above 80%, indicating that in the application process of lithium negative electrode, it can adapt well to the volume expansion of the negative electrode and avoid the increase of the overall impedance of the battery.
[0156] It can be seen from Example 1 and Comparative Example 1 that too little ammonium ions will lead to insufficient initiator, and the acrylate monomer cannot be added and polymerized to form an elastomer; while the ammonium ions in Comparative Example 2 are excessive, which affects the lithium ion transport, resulting in a decrease in lithium ion conductivity, tensile strength and elastic recovery rate. Therefore, the ammonium ions need to be maintained in an appropriate amount so that the composite electrolyte can obtain the best performance.
[0157] It can be seen from Examples 1 and 4 and Comparative Examples 3 and 4 that if the composite electrolyte membrane wants to obtain good performance, its monomer, cross-linking agent and plasticizer need to maintain a certain ratio, otherwise it will affect the various properties of the electrolyte membrane, especially the tensile strength and elastic recovery rate.
[0158] It can be seen from Examples 1, 5, 6 and Comparative Examples 5 and 6 that excessive or insufficient lithium salt will lead to reduced performance of the electrolyte membrane.
[0159] It can be seen from Example 1 and Comparative Examples 7 and 8 that the tensile strength of Example 1 is much greater than that of Comparative Examples 7 and 8. In Comparative Example 7, the proportion of the non-metallic cation-modified garnet electrolyte is too small, resulting in reduced tensile strength and elastic recovery rate. In Comparative Example 8, the proportion of the non-metallic cation-modified garnet electrolyte is too high, resulting in the inability to form the electrolyte membrane, resulting in its inability to be used as an ion conductor membrane.
[0160] Combining Example 1 and Comparative Example 9, it can be seen that the ionic conductivity and elastic recovery rate of Example 1 are greater than those of Comparative Example 9. This is because there is residual azobisisobutyronitrile initiator in Comparative Example 9, which leads to a decrease in ionic conductivity and elastic recovery rate; the tensile strength of Example 1 is greater than that of Comparative Example 9. This is because there is hydrogen bonding between the excess ammonium ions pinned on the ceramic surface and the copolymer, which enhances its tensile strength and improves its film-forming performance.
[0161] according to Figure 2 It can be seen that the deformation rates of Examples 1, 2, 3 and Comparative Example 2 are 293%, 265%, 331%, and 147%, respectively, and the tensile strengths are 0.83, 0.75, 0.9, and 0.58 MPa, respectively. The greater the deformation rate, the greater the tensile strength of the electrolyte membrane, and the better the strength of the electrolyte membrane. By comparing Examples 1, 2, and 3, Comparative Examples 1 and 2, it can be seen that excessive or insufficient non-metallic cations will lead to poor mechanical properties of the electrolyte membrane.
[0162] It can be seen that the high ion flux solid electrolyte membrane provided in the embodiment of the present application not only has excellent mechanical strength to ensure film-forming performance, but also can increase the compatibility between ceramics and polymers and improve ionic conductivity. At the same time, it will not introduce additional initiators, avoid initiator residues, and improve the electrochemical properties of the electrolyte.
[0163] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.
Claims
1. A high ion flux composite material, characterized in that: The invention comprises a non-metal cation-modified garnet electrolyte and a binder, wherein the binder comprises an acrylate copolymer and a lithium salt.
2. The high ion flux composite material according to claim 1, characterized in that: Calculated by mass fraction, the non-metal cation-modified garnet electrolyte accounts for 80-95%, and the adhesive accounts for 5-20%.
3. The high ion flux composite material according to claim 1, characterized in that: The non-metallic cations include NH4 + PH4 + One or more of the .
4. The high ion flux composite material according to claim 1, characterized in that: The molar ratio of the non-metallic cation to the garnet electrolyte is (30-100):
1.
5. The high ion flux composite material according to claim 1, characterized in that: The garnet electrolyte is an amorphous garnet electrolyte nano powder formed by crushing a single crystal garnet electrolyte.
6. The high ion flux composite material according to claim 1, characterized in that: The garnet electrolyte includes LGLZO electrolyte Li 6.4 Ga 0.2 La3Zr2O 12 ,LLZO electrolyte Li7La3Zr2O 12 and LLZTO electrolyte Li 6.5 LqCy 1.5 Ta 0.5 O 12 One or more of the .
7. The high ion flux composite material according to claim 1, characterized in that: The lithium salt includes one or more of lithium hexafluorophosphate, lithium bis(oxalatoborate), lithium bis(trifluoromethanesulfonyl imide) and lithium bis(fluorosulfonyl imide).
8. The high ion flux composite material according to claim 7, characterized in that: The lithium salt is lithium bis(trifluoromethanesulfonyl)imide.
9. The high ion flux composite material according to claim 1, characterized in that: In the adhesive, the mass fraction of the lithium salt is 25% to 35%.
10. The high ion flux composite material according to claim 1, characterized in that: The acrylic ester copolymer comprises a monomer, a cross-linking agent and a plasticizer, wherein the monomer, the cross-linking agent and the plasticizer all have an acrylic acid group, and the molar ratio of the monomer, the cross-linking agent and the plasticizer is (10-12):(3-5):(3-5).
11. The high ion flux composite material according to claim 10, characterized in that: The molar ratio of the crosslinking agent to the plasticizer is 1:
1.
12. The high ion flux composite material according to claim 10, characterized in that: The monomers include one or more of hexafluorobutyl acrylate, 3-(N,N-dimethylamino)ethyl acrylate, 2-methylcyanoacrylate, and azoacrylate.
13. The high ion flux composite material according to claim 10, characterized in that: The crosslinking agent includes one or more of ethyl acrylate, butanediol dimethacrylate, ethylene glycol dimethacrylate, and trimethylolacrylate.
14. The high ion flux composite material according to claim 10, characterized in that: The plasticizer includes one or more of lauryl acrylate, 2-methyl methacrylate, methyl acrylate, ethyl acrylate and isooctyl acrylate.
15. A method for preparing a high ion flux composite material according to any one of claims 1 to 14, characterized in that: It includes: Adding the non-metal cation-modified garnet electrolyte to the precursor solution of the adhesive and mixing well; The heating is used to carry out a curing polyaddition reaction to obtain a high ion flux composite material.
16. The method for preparing a high ion flux composite material according to claim 15, characterized in that: The heating temperature of the curing addition polymerization reaction is 90-120° C., and the heating time is 4-7 hours.
17. The method for preparing a high ion flux composite material according to claim 15, characterized in that: The preparation steps of the non-metal cation modified garnet electrolyte include: Amorphous garnet electrolyte nanopowder formed by crushing single crystal garnet electrolyte; dispersing amorphous garnet electrolyte nanopowder into a modification solution containing non-metallic cations and stirring; The garnet electrolyte modified by the non-metal cation is obtained by washing with a volatile solvent and drying.
18. The method for preparing a high ion flux composite material according to claim 15, characterized in that: The acrylate copolymer comprises a monomer, a cross-linking agent and a plasticizer, wherein the monomer, the cross-linking agent and the plasticizer all have an acrylic acid group. The steps for preparing the precursor solution of the adhesive include: The monomer, cross-linking agent, plasticizer and lithium salt are stirred and mixed evenly under light-proof conditions and allowed to stand.
19. A solid electrolyte membrane, characterized in that: It comprises the high ion flux composite material according to any one of claims 1 to 14.
20. A battery, characterized in that: It comprises the solid electrolyte membrane as claimed in claim 19.
